How China took on the United States and Europe at the WTO - SHAFFER, Gregory (Institutional Knowledge at Singapore Management University, 2021)
In joining the World Trade Organization in December 2001, China assumed vast legal commitments that significantly affected its internal laws and institutions. Western countries hoped to transform China and integrate it into a liberal, capitalist global economy.1 Many of China’s leaders aimed to use the process for internal reform as well. Nonetheless, they wished to do so on their own terms, and they faced considerable opposition internally. The government invested massively in developing legal capacity, including to adjust to WTO requirements that the United States had pressed upon it. In the process, China learned how to defend its interests through the WTO and to use the rules against the United States and the European Union. China’s responses affected US and European perceptions of the legal order, and the US reaction, in turn, has eroded it. As China grew economically and benefited from liberalized trade, as the 2008 financial crisis humbled American-style neoliberalism and raised China’s profile, and as President Xi assumed power and favored a growing role for the state and state-owned enterprises, what had seemed a tough deal for China in its WTO Accession Protocol increasingly appeared to many in the United States to be unfair to the United States.